Acid-Sensing Ion Channels and Pain - Gu, Qihai (MDPI, 2010)
Pathophysiological conditions such as inflammation, ischemia, infection and tissue injury can all evoke pain, and each is accompanied by local acidosis. Acid sensing ion channels (ASICs) are proton-gated cation channels expressed in both central and peripheral nervous systems. Increasing evidence suggests that ASICs represent essential sensors for tissue acidosis-related pain. This review provides an update on the role of ASICs in pain sensation and discusses their therapeutic potential for pain management.